Strictly Lobar Cerebral Microbleeds Are Associated With Cognitive Impairment. Issue 10 (October 2016) - Chung, Chih-Ping; Chou, Kun-Hsien; Chen, Wei-Ta; Liu, Li-Kuo; Lee, Wei-Ju; Chen, Liang-Kung; Lin, Ching-Po; Wang, Pei-Ning
Abstract : Background and Purpose—: Different distributions of cerebral microbleeds (CMBs) are associated with distinct pathological mechanisms. Lobar CMBs are thought to be related to cerebral amyloid angiopathy, whereas deep or infratentorial CMBs are related to hypertensive vasculopathy. The present study aimed to evaluate the effects of CMBs and their locations on a variety of cognitive domains. Methods—: Study subjects were selected from the community-based I-Lan Longitudinal Aging Study. We assessed cognitive domains, including verbal memory, language, visuospatial executive function, and verbal executive function. CMBs were evaluated using 3T susceptibility-weighted magnetic resonance imaging. Results—: We studied 959 subjects (mean±SD, 62.5±8.6 years; 425 [44.3%] men). CMBs were found in 14.2% of the population. We classified subjects with CMBs into 2 different groups based on the locations of their CMBs: (1) deep or infratentorial (85 subjects, 8.8% of population) and (2) strictly lobar (49, 5.1%). Multivariate linear analysis showed that strictly lobar CMBs were significantly associated with deficits in global cognitive function (Mini-Mental State Examination) and visuospatial executive function, as determined by the copy test of the Taylor complex figure test and the clock drawing test. We adjusted our results for age, sex, years of education, cardiovascular risk factors, and other markers of cerebral small vessel disease, lacunes, and white matter hyperintensity. Deep or infratentorial CMBs were not associated with changes in cognitive function in our population. Conclusions—: Strictly lobar, but not deep or infratentorial, CMBs are associated with changes in cognitive function, especially in visuospatial executive functions. Cerebral amyloid angiopathy may be the underlying pathology associated with CMB-related cognitive impairment. Abstract : Supplemental Digital Content is available in the text.